Stress and Damage Distribution Analysis of Steel Reinforced Geopolymer Concrete Beams: Finite Element Method and Experimental Comparison Under Varying Design Parameters - Ozbayrak, Ahmet; Kucukgoncu, Hurmet; Aslanbay, Huseyin Hilmi; Aslanbay, Yuksel Gul (Elsevier, 2025)
Geopolymer concrete (GPC) is a sustainable and eco-friendly alternative to ordinary Portland cement-based concrete (OPC). However, its application in reinforced concrete structures remains limited due to insufficient research on structural performance. This study examines the effects of tensile reinforcement ratio, sodium silicate/sodium hydroxide ratio, and curing method on GPCreinforced concrete (GPC-RC) beams. Experimental and numerical bending tests were performed on GPC and OPC beams with similar tensile reinforcement and strength properties. Load- displacement and moment-curvature relationships were obtained and compared, while stress and stiffness behaviors were analyzed numerically. The results show that curing methods and reinforcement ratios significantly influence GPC beam behavior. In GPC samples, numerical and experimental displacement and load values differed by approximately 10 % at both yield and ultimate points. For OPC, these differences were 35 % and 14 % at the yield point and 17 % and 25 % at the ultimate point. GPC exhibited distinct stress and damage distribution characteristics compared to OPC. The finite element models were statistically validated, confirming their consistency with experimental results. These findings contribute to the understanding of GPC's structural behavior and provide guidance for its design and optimization in reinforced concrete applications.
Ozbayrak, Ahmet/0000-0002-8091-4990; Kucukgoncu, Hurmet/0000-0001-5148-8753;
Keywords: Geopolymer Reinforced Concrete Beam; Experimental and Numerical Study; Structural Behavior; FEA; Stress and Damage Distribution